2015
DOI: 10.1186/s12888-015-0545-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of suicide attempters and ideators among acutely admitted psychiatric hospital patients in northwest Russia and northern Norway

Abstract: BackgroundMore knowledge about suicidality and suicide risk profiles in acute psychiatric hospital patients (both first-time and chronic patients) is needed. While numerous factors are associated with suicidality in such populations, these may differ across cultures. Better understanding of factors underlying suicide risk can be informed by cross-cultural studies, and can aid development of therapeutic and preventive measures.MethodsAn explorative, cross-sectional cohort study was carried out. Acutely admitted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 32 publications
(44 reference statements)
3
13
0
Order By: Relevance
“…Findings from the Northern Russia and Northern Norway show less reported suicidal ideation among patients and professionals in Northern Russia, especial among men, despite the higher suicidal rates, particular in men. Failure to acknowledge and communicate suicidal ideation is suspected to be a risk factor for suicide [ 18 , 20 ]. Stigmatic attitudes and little awareness of suicidal ideation might hinder patients to get help to be aware needed changes to get a better life.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Findings from the Northern Russia and Northern Norway show less reported suicidal ideation among patients and professionals in Northern Russia, especial among men, despite the higher suicidal rates, particular in men. Failure to acknowledge and communicate suicidal ideation is suspected to be a risk factor for suicide [ 18 , 20 ]. Stigmatic attitudes and little awareness of suicidal ideation might hinder patients to get help to be aware needed changes to get a better life.…”
Section: Discussionmentioning
confidence: 99%
“…Psychiatric disorders were considered the most important causes of suicide in both cities in line with previous studies that highlights mental illness as main reason for suicide [ 10 ]. But suicides have many causes, and a study from Northern Russia and Northern Norway found that suicide were less associated with severe mental illness in Russia than Norway [ 18 ]. The World Health Organization has stated that mental disorder and harmful use of alcohol contribute to many suicides worldwide [ 1 ], also described in several studies [ 38 – 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that the negative perception of suicide given by participants may be relatedeither directly or indirectlyto the teachings of Confucianism. Suicide is considered a violation of Confucian teachings, and a person who expresses suicidal ideation or actively seeks to die by suicide would be at increased risk of becoming marginalized and disenfranchised (Sørlie et al 2015). Based on the cultural theory and model of suicide, suicide behaviours would be reduced if they are defined as unacceptable or unethical in some cultures (Chu et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…During the period 1993–2010, the total population decrease was about 13 million people [ 1 ]. Non-communicable diseases such as high rates of mental illness, suicide, and alcohol abuse strongly contributed [ 2 – 4 ]. In a Russian cultural context, alcohol abuse may function more as escape from negative emotions and suicidality than in a Western Norwegian context [ 4 ], with negative implications for self-regulation, help-seeking behaviour and suicide rates.…”
Section: Introductionmentioning
confidence: 99%